Platform Standards, Collusion and Quality Incentives - Claudia Salim (Verein für Socialpolitik, 2010)
We present the idea that quality cooperation and standardisation might raise network providers' incentives for product differentiation. As a result, the equilibrium outcome may be characterised by voluntary standardisation and maximum quality differentiation: This situation arises, if platforms compete in prices, but coordinate their quality provision, while the cost of quality provision is rather low. The result implies that firms might jointly agree to quality differences in order to offset consumers' taste for variety. Collusive qualities and standardization are socially more desirable than exclusivity with regard to investments. Nevertheless, quality competition and standardisation achieves the highest investments and maximum welfare.
Keywords: D43; D62; L13; 330; two-sided markets; standards; collusion; investment in transaction quality